Ethanol Assisted Transfer for Clean Assembly of 2D Building Blocks and Suspended Structures. (6th May 2019) - Yang, Xin; Li, Xiuqiang; Deng, Yu; Wang, Yuxi; Liu, Guoliang; Wei, Cong; Li, Hai; Wu, Zhen; Zheng, Qinghui; Chen, Zhiwen; Jiang, Qing; Lu, Haiming; et al.
Abstract: As two dimensional materials (2D materials) demonstrate unique and diverse properties, clean transfer methods can serve a cornerstone for creative assembly of these 2D building blocks for both fundamental explorations and versatile applications. One of the major challenges for preserving the pristine properties of 2D materials during transfer and construction is to debond 2D materials from original substrates without inducing structural damage and external contamination. In this work, through both molecular dynamic studies and experimental demonstration, it is found that droplets of ethanol, a common and environmental friendly solvent, can be used to effectively reduce the adhesion energy between 2D materials and substrates, and therefore enable a clean transfer method for 2D mterials. Various assembled structures based on 2D building blocks, such as van der Waals heterostructures, predesigned artificial patterns, 2D materials on suspended devices are all demonstrated. Thermal conductivity measurements of MoS2 nanosheets on a suspended microbridge device also confirm the successful application of suspended 2D transfer. It is expected that this ethanol assisted transfer method can enable clean assembly of 2D building blocks for construction of novel structures and suspended devices. Abstract : An ethanol assisted transfer method for transferring two dimensional materials is favorable for the exploration of intrinsic properties. Various van der Waals heterostrustures, predefined patterns, suspended samples can be assembled based on this method. Furthermore, thermal conductivity at room‐temperature of 52 W m −1 K −1 for five layer MoS2 is measured on a suspended microbridge device using this clean transfer method.